Modern trends in liquid state theory: a Festschrift for Yurij Kalyuzhnyi - Holovko, M. (Condensed Matter Physics, 2011)
On July 20, 2011 Yurij Kalyuzhnyi celebrated his 60th birthday. On this occasion the Editorial Board of ''Condensed Matter Physics`` decided to honour him with a collection of scientific papers. Numerous researchers, colleagues and co-workers of Yura have gladly contributed their articles. On behalf of the ''Condensed Matter Physics`` Editorial Board, I want to express sincere gratitude to all of them. Highly skilled contributions reflect the modern development of liquid state theory in different areas which are close to Yu. Kalyuzhnyi's interests during many years of his scientific activity.